Characterization of 2009 Pandemic Influenza A (H1N1) Virus Specimens with a Positive Hemagglutinin 1 Signal in the Luminex xTAG Respiratory Viral Panel Assay - McCloskey, Cindy B. (American Society for Microbiology, 2011)
This retrospective review analyzed Luminex xTAG respiratory viral panel (RVP) results for 2009 pandemic influenza A (H1N1) virus specimens. Comparing median fluorescence intensity (MFI) signals for the influenza A virus and hemagglutinin 1 (H1) reactions for specimens with very low positive (MFI < 1,000) or “no-call” H1 results reliably distinguished 2009 H1N1 from seasonal virus.